KAJIAN TINGKAH LAKU IKAN TERHADAP ALAT TANGKAP GILL NET - Muhammad Syahdan (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2010)
Knowledge about fish behaviour be factor important in determine success of operation catching because i this related to characteristics a target catching either through physical also the biological. Part from tool catch gill net influence behaviour fish there is six factor there are twine net, Strains distance body net, Shortening, Tall net, mesh size and Colour net. Target catching is fish pelagis in two condition, That is of condition net passive cause fish trapp with hooking part the fish gills while when net in a condition mobile so fish inclined trapp according to belit in body net. Efforts catching can do towards kind fish demersal that is with increase gravity net so that not formed ante-room part under net under of the sea. Limit maximum depth swimming a kind fish be matter important in determine success efforts catching. Keywords: Behaviour fish, Gill net